Transient Absorption Spectra of Metal‐Free and Transition‐Metal 5, 10, 15, 20‐Tetraferrocene Porphyrins: Influence of the Central Metal Ion, Solvent Polarity, and the Axial Ferrocene Ligand. Issue 13 (12th April 2022) - Schrage, Briana R.; Ermilov, Eugeny; Nemykin, Victor N.
Abstract: The transient absorption spectra of the series of diamagnetic H2 TFcP, ZnTFcP, PdTFcP, and FcInTFcP compounds (TFcP(2‐)=5, 10, 15, 20‐tetraferroceneporphyrin dianion) were investigated in polar (DMF) and non‐polar (toluene) solvents using excitation at 650 nm. The formation and the deactivation of the charge‐separated (Fc + ‐Porphyrin −. ) state were observed in all cases. The lifetime of the charge‐separated state is nearly constant for all compounds (∼20 ps) and independent of the nature of the central ion and solvent. The formation of the triplet state in all the complexes was not observed. The third, minor long‐lived (160–480 ps) component was observed in polar DMF solvent. This component was tentatively assigned to the porphyrin species that are weakly bound to the carbonyl oxygen in DMF. DFT and TDDFT calculations on the ground state, excited state, and triplet state of the target compounds were in agreement with the experimental data. Abstract : The transient absorption spectra of H2 TFcP, ZnTFcP, PdTFcP, and FcInTFcP was investigated in polar and non‐polar solvents using excitation at 532 or 650 nm. The formation and the deactivation of the charge‐separated (Fc + ‐Porph −. ) state were observed in all cases. The lifetime of the charge‐separated state is nearly constant (∼20 ps) and independent of the nature of the central ion and solvent.